Mechanism of HIFs in osteoarthritis - Zhang, Xin-An; Kong, Hui (Frontiers in Immunology, 2023)
Osteoarthritis (OA) is a common disabling disease which has a high incidence rate in the elderly. Studies have found that many factors are involved in the pathogenesis of OA. Hypoxia-inducible factors (HIFs) are core regulators that induce hypoxia genes, repair the cellular oxygen environment, and play an important role in the treatment of OA. For example, HIF-1α can maintain the stability of the articular cartilage matrix, HIF-2α is able to cause chondrocyte apoptosis and intensify in-flammatory response, and HIF-3α may be the target gene of HIF-1α and HIF-2α, thereby playing a negative regulatory role. This review examines the mechanism of HIFs in cartilage extracellular matrix degradation, apoptosis, inflammatory reaction, autophagy and then further expounds on the roles of HIFs in OA, consequently providing theoretical support for the pathogenesis of OA and a new target for OA treatment.